Editorial: the diminishing returns of normalisation of the oesophageal mucosa―Authors' reply. Issue 1 (7th June 2017) - Mastracci, L.; Fiocca, R.; Engstrom, C.; Attwood, S.; Ell, C.; Galmiche, J. P.; Hatlebakk, J. G.; Långström, G.; Eklund, S.; Lind, T.; Lundell, L.
Abstract : Linked Content This article is linked to Mastracci et al and Genta papers. To view these articles visithttps://doi.org/10.1111/apt.14038 andhttps://doi.org/10.1111/apt.14097 .